Sociodemographic differences in fast food price sensitivity - Meyer, Katie A. (2014)
IMPORTANCE: Fiscal food policies (e.g., taxation) are increasingly proposed to improve population-level health, but their impact on health disparities is unknown. OBJECTIVE: We estimated subgroup-specific effects of fast food price changes on fast food consumption and cardio-metabolic outcomes, hypothesizing inverse associations between fast food price with fast food consumption, BMI, and insulin resistance and stronger associations among blacks (vs. whites) and participants with relatively lower education or income. DESIGN: 20-year follow-up (5 exams) in a biracial U.S. prospective cohort: Coronary Artery Risk Development in Young Adults (CARDIA) (1985/86–2005/06, baseline n=5,115). PARTICIPANTS: Aged 18–30 at baseline; designed for equal recruitment by race (black/white), educational attainment, age, and gender. EXPOSURES: Community-level price data from the Council for Community and Economic Research (C2ER) temporally- and geographically-linked to study participants’ home address at each exam. MAIN OUTCOME AND MEASURES: Participant-reported number of fast food eating occasions per week; BMI (kg/m(2)) from clinical assessment of weight and height; homeostatic model assessment insulin resistance (HOMA-IR) from fasting glucose and insulin. Covariates included individual- and community-level social and demographic factors. RESULTS: In repeated measures regression, multivariable-adjusted associations between fast food price and consumption were non-linear (quadratic, p<0.001), with significant inverse estimated effects on consumption at higher prices; estimates varied according to race (interaction term p=0.04), income (p=0.07), and education (p=0.03). For example, at the 10(th) percentile of price ($1.25/serving), blacks and whites had mean fast food consumption (times/week) of 2.2 (95% CI: 2.1–2.3) and 1.6 (1.5–1.7), respectively, while at the 90(th) percentile of price ($1.53/serving), respective mean consumption estimates were 1.9 (1.8–2.0) and 1.5 (1.4–1.6). We observed differential price effects on HOMA-IR (inverse for lower educational status and at middle income) and BMI (inverse for blacks, lower education, and middle income; positive for whites, high education, and high income). CONCLUSIONS: We found greater fast food price sensitivity on fast food consumption and insulin resistance among sociodemographic groups that have a disproportionate burden of chronic disease. Our findings have implications for fiscal policy approaches related to diet, particularly with respect to possible effects of fast food taxes among populations with diet-related health disparities.